REFLEKSI ATAS BEBERAPA ISU KEBIAJAKAN PENDIDIKAN - Makmuri Sukarno (Jurnal Kependudukan Indonesia, 2007)
Although SBY-JK's government has been sharpern in responding to the demand for basic education, nevertherless, the utilization of schooVmadrasah's autonomy for accummating money from the community as an in-put, mostly in secondary level, was lacking in accountability and public political participation and tending to excarcerbate social gap in education. Therefore, issues on out-put, public accountability and widening the chance of those who have not enough financial supports are becoming great challanges in the future. Accordingly, government's policy on these issues need to be delivered through an eduquate system.